Qualitative study of factors affecting engagement with a hospital-based violence intervention programme in Indianapolis, Indiana - Malaz Boustani; Lauren A Magee; Damaris Ortiz; Zachary W Adams; Brigid R Marriott; Reilin J Moore; Blakney Q Brooks; Clark J Simons (BMJ Public Health)
Background There are few qualitative studies of firearm injury survivors and hospital-based violence intervention programme (HVIP) participants. The original study aimed to identify facilitators and barriers to survivors’ utilisation of mental health services. This secondary analysis aimed to identify factors that may impact engagement with an HVIP.Study design This study was a subanalysis of an original qualitative study that used a community-based participatory research approach to conduct semistructured interviews with English-speaking, intentional firearm injury survivors aged 13 and older within Indianapolis, Indiana between 2021 and 2022. Participants were recruited by a community organisation through a snowball sampling method. Interviews were analysed using manual thematic analysis. Themes were analysed and discussed in relation to HVIPs.Results A total of 18 interviews were completed. The majority of participants identified as black (17/18, 94.4%). Nearly all (75%) participants were between the ages of 13 and 24 years of age at the time of their shooting. During content analysis, five themes were identified: (1) delayed readiness to change, (2) desire for independence, (3) lack of trust, (4) persistent emotional and physical effects of trauma and (5) unawareness of HVIP resources.Conclusions This qualitative analysis of firearm injury survivor experiences provided insights for improved engagement with HVIPs. Continued pursuit of survivors for several years after their injury, improved dissemination of resources, establishing trust, and addressing persistent physical and psychological symptoms while respecting participants’ desire for independence may lead to increased engagement of firearm injury survivors with HVIPs.